Nutrient budgeting and nutrient balance under high density planting system in cashew (Anacardium occidentale) - YADUKUMAR, N; REJANI, R; NANDAN, S L; PRABHAKAR, B (The Indian Journal of Agricultural Sciences, 2013)
Â The study on nutrient budgeting and nutrient balance was conducted to determine the optimal fertilizer requirementfor cashew (Anacardium occidentale L.) under high-density planting system in relation to yield and net profit. The sixyearold plantation of cashew Bhaskara variety under high-density planting system (625 trees/ha) was used. A negative N,P and K balance of 113, 22 and 45 kg/ha/year was found in the control plot where no fertilizers were applied. A strongpositive N balance ranged from 137 to 251, P balance from 34 to 75 and K balance from 89 to 164 kg/ha/year were foundin trees with two-thirds and full doses of fertilizer treatments. In treatments with one-third dose of fertilizers, a positive N,P and K balance of 40, 19 and 40 kg/ha/year were found. This indicates that in high-density planting system, existingfertilizer schedule, viz. recommended dose of fertilizers (RDF) is on higher side and optimal dose of fertilizer required isonly one-third of the RDF. The yield and net profit in full dose and one-third dose of fertilizer treatments were on par. Thehigher yield of 1.47 and 1.41 tonnes/ha/year and a net profit of Rs.40 030 and `Rs 41 274/ha/year were obtained in these twotreatments. The application of one-third dose of fertilizer to soil instead of recommended dose of fertilizer not only helpsto reduce the input required and cost of cultivation but also the ecological hazards arising from excess inorganic fertilizerapplication. Hence, one-third dose of fertilizer is optimal for cashew plantation under high-density planting system.